Atrial Fibrillation Caused by Intractable Hiccups: A Unique Cause and Cure - Joshua H. Arnold; Neil Brandon (Case Reports in Pulmonology)
We present the case of a 61-year-old male who developed persistent hiccups concurrently with the onset of atrial fibrillation (AF). The hiccups were refractory to traditional treatment but resolved immediately upon electrical cardioversion (ECV) to normal sinus rhythm (NSR). The patient has remained in NSR and free of hiccups. The potential etiologies for hiccups are numerous and varied, and the management of persistent hiccups can be difficult. Cardiac associations including myocardial infarction and pericarditis have been described, while few cases of first-time onset of atrial fibrillation leading to hiccups have been documented. This case discusses a unique instance demonstrating a connection between hiccups and cardiac pathology and an overview of its management.